2015
DOI: 10.1159/000368367
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Bronchoscopic Microsample Probe versus Bronchoalveolar Lavage in Patients with Burns-Related Inhalational Injury, Acute Lung Injury and Chronic Stable Lung Disease

Abstract: Background and Objectives: The bronchoscopic microsample (BMS) probe allows direct epithelial lining fluid (ELF) level measurement without saline lavage. We investigated whether cytokine levels in ELF from a BMS differed from those obtained by bronchoalveolar lavage (BAL) in stable and acute lung disease. Methods: In a single-centre, prospective observational cohort study of 45 patients, a sequential BMS probe procedure and BAL were performed on patients with stable chronic obstructive lung disease, interstiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…To investigate whether the protective effect of TBMS1 against PM 2.5 -induced pulmonary injury was associated with inflammation, TNF-α and IL-6 levels were measured. These proinflammatory cytokines are known to be elevated in the BALF of lung disease patients (23). The present study revealed that TBMS1 treatment significantly decreased TNF-α and IL-6 protein in BALF.…”
Section: Discussionsupporting
confidence: 62%
“…To investigate whether the protective effect of TBMS1 against PM 2.5 -induced pulmonary injury was associated with inflammation, TNF-α and IL-6 levels were measured. These proinflammatory cytokines are known to be elevated in the BALF of lung disease patients (23). The present study revealed that TBMS1 treatment significantly decreased TNF-α and IL-6 protein in BALF.…”
Section: Discussionsupporting
confidence: 62%
“…Increased levels of TNFα have been detected in BAL, serum and epithelial lining fluid from patients with ALI and ARDS (Antonelli et al, 1994; Bauer et al, 2000; Hamacher et al, 2002; Li et al, 2010; Reper and Heijmans, 2015; Roten et al, 1991; Singh et al, 2015; Suter et al, 1992; Vaillant et al, 1996). Higher serum levels of TNFα during early stages of ALI are associated with increased mortality at 2–3 months (Makabe et al, 2012).…”
Section: Role Of Tnfα In Pulmonary Diseasesmentioning
confidence: 99%
“…Second, for a specific biomarker, the best way to collect an ideal biological sample should be verified. For example, several studies have reported that bronchoscopic microsampling yields a much higher concentration of inflammatory mediators than traditional bronchoalveolar lavage (BAL) methods [ 50 ]. Third, panels of biomarkers seem to be a more practical choice than a single marker.…”
Section: Discussionmentioning
confidence: 99%